Like a rolling stone: Colonization and migration dynamics of the gray reef shark (Carcharhinus amblyrhynchos). Issue 1 (10th January 2023) - Lesturgie, Pierre; Braun, Camrin D.; Clua, Eric; Mourier, Johann; Thorrold, Simon R.; Vignaud, Thomas; Planes, Serge; Mona, Stefano
Abstract: Designing appropriate management plans requires knowledge of both the dispersal ability and what has shaped the current distribution of the species under consideration. Here, we investigated the evolutionary history of the endangered gray reef shark ( Carcharhinus amblyrhynchos ) across its range by sequencing thousands of RADseq loci in 173 individuals in the Indo‐Pacific (IP). We first bring evidence of the occurrence of a range expansion (RE) originating close to the Indo‐Australian Archipelago (IAA) where two stepping‐stone waves (east and westward) colonized almost the entire IP. Coalescent modeling additionally highlighted a homogenous connectivity ( Nm 10 per generation) throughout the range, and isolation by distance model suggested the absence of barriers to dispersal despite the affinity of C. amblyrhynchos to coral reefs. This coincides with long‐distance swims previously recorded, suggesting that the strong genetic structure at the IP scale ( F ST 0.56 between its ends) is the consequence of its broad current distribution and organization in a large number of demes. Our results strongly suggest that management plans for the gray reef shark should be designed on a range‐wide rather than a local scale due to its continuous genetic structure. We further contrasted these results with those obtained previously for the sympatric but strictly lagoon‐associated Carcharhinus melanopterus, known for its restricted dispersal ability. Carcharhinus melanopterus exhibits a similar RE dynamic but is characterized by a stronger genetic structure and a nonhomogeneous connectivity largely dependent on local coral reefs availability. This sheds new light on shark evolution, emphasizing the roles of IAA as source of biodiversity and of life‐history traits in shaping the extent of genetic structure and diversity. Abstract : Carcharhinus amblyrhynchos is an endangered Indo‐Pacific reef shark, which shows reef fidelity but long‐distance movements, raising questions about connectivity patterns and the extent of conservation units. Using genomic data, we show that it has undergone a range expansion from the Indo‐Australian Archipelago (IAA) and is organized as a meta‐population characterized by homogeneous connectivity throughout its range. We highlight the low dependence of C. amblyrhynchos on reef availability and its ability to cross open sea expanses, which do not represent barriers to gene flow, contrasting with the sympatric Carcharhinus melanopterus, whose dispersal is strictly dependent on local reef distribution. Conversely, both species share similar range expansion dynamics, suggesting a major importance of the IAA as a source of biodiversity for reef sharks.